A mixed studies systematic review on the health and wellbeing effects, and underlying mechanisms, of online support groups for chronic conditions - Freya Mills; John Drury; Charlotte E. Hall; Dale Weston; Charles Symons; Richard Amlôt; Holly Carter (Communications Psychology)
Abstract This pre-registered systematic review aimed to examine whether online support groups affect the health and wellbeing of individuals with a chronic condition, and what mechanisms may influence such effects. In September 2024, literature searches were conducted across electronic databases (Medline, Embase, PsycInfo, Web of Science and Google Scholar), pre-publication websites (MedRxiv and PsyArXiv) and grey literature websites. Qualitative and quantitative studies were included if they explored the impact of online support groups on the health and wellbeing outcomes of individuals with a chronic condition. The Mixed Methods Appraisal Tool was used to appraise the quality of the included studies. In total 100 papers met the inclusion criteria with their findings presented in a thematic synthesis. Health and wellbeing outcomes were categorised as: physical health, mental health, quality of life, social wellbeing, behaviour and decision-making, and adjustment. Mechanisms reported in these studies related to exchanging support, sharing experiences, content expression, and social comparison. User and group characteristics were also explored. The included studies suggest that online support groups can have a positive impact on social wellbeing, behaviour, and adjustment, with inconclusive findings for physical health and quality of life. However, there is also the possibility of a negative effect on anxiety and distress, particularly when exposed to other group members’ difficult experiences. Research comparing different online group features, such as platforms, size, and duration is needed. In particular, future research should be experimental to overcome the limitations of some of the cross-sectional designs of the included studies. The review was funded by the National Institute for Health and Care Research Health Protection Research in Emergency Preparedness and Response. Pre-registration ID: CRD42023399258